The Effect of V and X Groove Configurations in SMAW Welding on the Hardness of Low-Carbon Steel - Irlando Raymond Hamri Waridin; Nody Poluan Sompie (Global Writing Academica Researching and Publishing, 2026)
This study compared the distribution of Rockwell A hardness in SMAW joints with V- and X-grooves made from 10 mm low-carbon steel plates. Welding used 3.2 mm AWS E7016/LB 52U electrodes. Three specimens were prepared for each groove, and hardness was measured at three points in the base metal, heat-affected zone (HAZ), and weld metal. The data were analyzed descriptively using specimen means and combined means for each region. The X-groove produced higher combined means than the V-groove in the base metal (80.92 versus 77.52 HRA), HAZ (81.85 versus 79.77 HRA), and weld metal (83.92 versus 81.98 HRA). The highest regional mean was approximately 84.16 HRA in the weld metal of specimen X3, whereas the highest value for the V-groove was 83.06 HRA in the weld metal of specimen V3. Both groove types showed an increase in hardness from the base metal toward the weld metal. Under the conditions of this study, the X-groove was associated with a higher hardness profile; however, this finding cannot be generalized as superior joint strength because only hardness was measured.